2021
DOI: 10.1155/2021/3570523
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of In Situ Stress Distribution on the Stability of Roadway Surrounding Rock

Abstract: In order to understand the instability characteristics of surrounding rock in the process of deep roadway excavation, a three-dimensional numerical model was established by FLAC3D to systematically analyze the influence of roadway surrounding rock stability under different in situ stress distribution forms, and the environmental coefficient of mining-induced stress η was defined, the larger the environmental coefficient of mining-induced stress is, the larger the surrounding rock stress environment is, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Zhao et al proposed that under the infuence of self-weight and roof pressure, the coal wall was mainly in the form of tension failure and shear failure, and a method to determine the support working resistance based on the control of the roof and coal wall was given [25][26][27]. Chen et al found through the compressive strength test that when the layering was developed, and there were many weak planes in the coal seam, the coal seam with a low hardness coefcient was more likely to lead to rib spalling, and the fexible reinforcement technology for the prevention and control of ultra-high rib spalling was proposed [1,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al proposed that under the infuence of self-weight and roof pressure, the coal wall was mainly in the form of tension failure and shear failure, and a method to determine the support working resistance based on the control of the roof and coal wall was given [25][26][27]. Chen et al found through the compressive strength test that when the layering was developed, and there were many weak planes in the coal seam, the coal seam with a low hardness coefcient was more likely to lead to rib spalling, and the fexible reinforcement technology for the prevention and control of ultra-high rib spalling was proposed [1,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al proposed that in situ stress measurements should select measuring points according to rock mass structures and should avoid interference sources, such as stress fields and unstable regions, to ensure the authenticity of the stress data. Their theory played a guiding role in the selection of the Xiling mining area in Sanshandao as the drilling location [13]. Based on the measurements of the in situ stress field of a specific mine in Jiaodong, it was found that the stress in the deep mining area is mainly horizontal tectonic stress [14], and proper support was suggested to be provided in time.…”
Section: Introductionmentioning
confidence: 99%